2015
DOI: 10.1038/ncomms8338
|View full text |Cite
|
Sign up to set email alerts
|

A lead-halide perovskite molecular ferroelectric semiconductor

Abstract: Inorganic semiconductor ferroelectrics such as BiFeO3 have shown great potential in photovoltaic and other applications. Currently, semiconducting properties and the corresponding application in optoelectronic devices of hybrid organo-plumbate or stannate are a hot topic of academic research; more and more of such hybrids have been synthesized. Structurally, these hybrids are suitable for exploration of ferroelectricity. Therefore, the design of molecular ferroelectric semiconductors based on these hybrids pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
387
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 600 publications
(411 citation statements)
references
References 69 publications
23
387
0
1
Order By: Relevance
“…[51][52][53] More ferroelectric structures have been proposed for various metal, cation or halogen, among which one can find simple examples in Amm2, R3m or Cmc2 1 . 27,47,50,[54][55][56] For 3D materials containing Ge, the tolerance factor is more compatible with the onset of a polar distortion, and a sizable SOC may also be present, especially with the contribution of heavy halogen atoms. 57 More complex cases may correspond to combinations of both antiferrodistortions and ferroelectric behavior.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…[51][52][53] More ferroelectric structures have been proposed for various metal, cation or halogen, among which one can find simple examples in Amm2, R3m or Cmc2 1 . 27,47,50,[54][55][56] For 3D materials containing Ge, the tolerance factor is more compatible with the onset of a polar distortion, and a sizable SOC may also be present, especially with the contribution of heavy halogen atoms. 57 More complex cases may correspond to combinations of both antiferrodistortions and ferroelectric behavior.…”
mentioning
confidence: 95%
“…Indeed, several compounds belong to polar groups and have been scrutinized. 7,29,56,64,65 One should notice that the above examples have a symmetry axis perpendicular to the staking direction. As a consequence, the Rashba effect is incomplete, i.e.…”
mentioning
confidence: 99%
“…The (ammoniomethyl)pyridinium cation has a structure similar to that of the benzylammonium cation, and the same rotation in the phase transition has been observed. 14 Therefore, the alignment of the organic cations is responsible for the ferroelectricity in 1. This is different from that in the three-dimensional methylammonium lead-halide perovskites.…”
Section: Resultsmentioning
confidence: 99%
“…We recently demonstrated that photoferroelectricity can be achieved in lead-halide perovskite-type ferroelectrics. 13,14 Although these compounds show excellent ferroelectricity, they have two drawbacks: a relatively high bandgap (42.7 eV) and toxicity from the Pb element. …”
mentioning
confidence: 99%
“…From both theoretical and applied viewpoints, phase-transition compounds are popular and valuable in increasing the general understanding of structure-property relations and exploring functional materials with novel physical properties [1][2][3][4][5][6][7][8][9][10]. Phase-transition crystalline materials are usually accompanied by an abrupt change in some physical properties around the transition temperature.…”
Section: Introductionmentioning
confidence: 99%